Community-Based Tourism Model Development in Increasing Community Involvement and Welfare: A Case Study of Huta Tinggi Village and Huta Bolon Samosir Village - Yenny, Novida; Elfayetti, Elfayetti; Delita, Fitra; Debyana, Debyana (Randwick International of Social Science Journal, 2024)
North Sumatra has tourism potential that is well known to foreign countries, one of the tourist objects is Lake Toba in the Samosir district. Lake Toba was formed from volcanic and tectonic processes and has carved extraordinary natural beauty so that it has become an attractive and well-known tourist destination not only by local tourists but also known by foreign tourists. Its natural beauty in the form of a lake surrounded by hills presents a view that is no less beautiful than Lake Toba itself and is an inseparable unit from the life of its people (known as the Toba Samosir people). This natural tourism potential can certainly be developed by utilizing local wisdom in the form of local customs and culture by involving the community to participate in developing tourism potential. The purpose of this study was to analyze the tourism potential in Huta Bolon and Huta Tinggi Village, Samosir Regency, evaluate community readiness for the development of community-based tourism and local government efforts to develop tourism in Huta Bolon and Huta Tinggi Village, Samosir Regency. community-based tourism development policies in Huta Bolon and Huta Tinggi Village, Samosir Regency. Outcomes to be achieved in this study. With this model, the problem of action and poverty in society can be resolved. This study used a survey method with locations in Huta Bolon and Huta Tinggi Village, Samosir Regency. Sources of data in this study are the village community, community leaders and village officials. Data collection was carried out using observation techniques, questionnaires, interviews and documentary studies. Data analysis was carried out with the stages of reduction, data presentation, and data verification. The results showed that the physical and social potential in Huta Bolon and Huta Tinggi Village could be developed for tourism. Moreover, the level of readiness of the community is relatively high. The formulation of the CBT model is called the CBT model RP3I (Community Based Tourism: Relationship, Planning, Producing, Promoting and Involvement).